Perspectives on preparation of two-dimensional MXenes - Ningjun Chen (Taylor & Francis Group, 2021)
The excellent intrinsic properties of two-dimensional MXenes, such as hydrophilic, good electrical and thermal conductivity, excellent film forming ability, render them potential candidates for many innovations in different areas. High-quality MXene plays an important role in enhancing the devices’ performances in various applications. However, the synthesis of high-quality MXenes has not been well documented. Herein, we summarize the up-to-date preparation strategies of MXene and compare their respective advantages and disadvantages. We particularly outline the criteria of high-quality MXenes, and focus on the influence of different synthetic methods on the surface functional groups, morphology (size and defect), layer spacing of MXene, etc. The challenges on MXenes’ preparation and their future perspectives are also provided. We anticipate this perspective will provide prospective guidance for synthesizing desirable high-quality MXenes.